Studi Akurasi Pengukuran GNSS Jaring Makro Tahun 2016 dan 2017 pada Pemantauan Bendungan Sermo - Muhammad Iqbal Taftazani; Yulaikhah Yulaikhah (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
Monitoring of deformation on Sermo Dam has been widely practiced. One of them is by installing the monitoring point, locate dinside the Sermo Dam area called the micro network, and outside the dam called macro network. The installation of the micro network monitoring point aims to monitor the deformation of the dam due to the volume of water. The macro network monitoring point aims to monitor the effect of the existence of an active fault under the dam. In the last few years, monitoring in Sermo Dam has been done using GNSS technology. This paper intends to present the results of the accuracy represented by the deviation standard value of the measurement point at the macro net on the GNSS observation in 2016 and 2017. The objective is to compare the accuracy resulting from various GNSS processing strategies in observation 2016 and 2017, evaluation of GNSS measurements that can be used as guidance in subsequent GNSS measurements. The result shows that GNSS measurement in 2017 using two IGS reference points (BAKO and COCO) has a better standard deviation value compared to the 2016 measurement by the difference 1-5 mm on the X axis, 1-9 mm on the Y axis, and 1-2 mm on the Z axis. In the GNSS data processing using seven IGS reference points (BAKO, COCO, KARR, DARW, GUUG, PIMO, SHAO) in 2016 mostly has a better standard deviation compared to 2017 measurement except in MAK5 with the difference 0-4 mm on the X axis, 1-10 mm on Y axis, and 0-2 mm on Z axis. As for the value of coordinate data processing in 2016 and 2017on the two processing strategies there are differences in coordinate values that indicate the movement of monitoring points of macro network. However, the vector of the point movement that occurs in the two strategies has a different direction. This requires verification in-depth research and focused on the deformation of the Sermo Dam monitoring point.